Methodological appraisal of the evidence about efficacy of metabolic surgery in adults with non-morbid obesity and hypertension: An overview of systematic reviews - Cáceres-Távara, María E. (2022)
Background: Nowadays, the high morbimortality of obesity is mainly related to diabetes, cancer, and hypertension. It is reported that obesity in patients with hypertension can lead to resistance to pressure reduction through pharmacological therapy and lifestyle changes, so bariatric surgery emerges as a proposed treatment for obesity. Methods: We performed an umbrella review that included systematic reviews of clinical trials that evaluated patients with hypertension and non-morbid obesity. The quality and certainty of the evidence was evaluated with the AMSTAR-II and GRADE tools. Results: 677 systematic reviews were identified, of which only three were included for analysis. We considered the outcomes addressed by the reviews on hypertension, identifying that 5 RCTs evaluated pressure reduction at 1 year of follow-up and 5 RCTs at more than 1 year, 5 RCTs evaluated hypertension rate, 6 RCTs analyzed changes in systolic pressure and 5 RCTs changes in diastolic pressure. Likewise, when assessing the methodological quality, it was concluded that the three reviews have critically low quality. Conclusions: We found only three systematic reviews that evaluated the topic with critically low methodological quality. They reported results in favor of metabolic surgery, but with very low certainty of evidence.